Evaluasi Penggunaan Obat Anti Hipertensi Pada Pasien Gagal Ginjal Kronik Dengan Hemodialisa Di Rsup Dr. Soeradji Tirtonegoro Klaten Tahun 2015 - Fakhrunnisa, Laksmi; , Dra. Nurul Mutmainah, M.Si., Apt (2016)
The complications of hypertension with kidney failure will further accelerate the development of the disease and increase the mortality rate of patients. The condition is considered as the basis for giving antihypertensive drugs toward patients with hemodialysis. This study was aimed to evaluate the use of antihypertensive drugs for the patients with chronic kidney failure with hemodialysis at Dr. Soeradji Tirtonegoro Hospital Klaten 2015. The data used in this study was obtained from the medical records of hypertensive patients with chronic kidney failure and undergoing hemodialysis at Dr. Soeradji Tirtonegoro Hospital Klaten 2015. The data were then analyzed descriptively by evaluating the therapy rationality the use of hypertensive patients with chronic kidney failure undergoing hemodialysis. The sample was taken by using purposive sampling method. The antihypertensive drug use was evaluated based on the right drug, the right patient xi and the right dosage. The data was analyzed descriptively according to The Drug Information Handbook 19th Edition 2010, 7th Joint National Committee of Hypertension 2004, and other literatures. From the 29 samples obtained in this study, his found that antihypertensive drug that most commonly used were furosemide 10,34%, irbesartan 3,44%, furosemide + amlodipine 3,44%, furosemide + valsartan 3,44%, amlodipine + candesartan 3,44%, valsartan + amlodipine 10,34%, furosemide + amlodipine + irbesartan 13,82%, furosemide + amlodipine + valsartan 48,30%, furosemide + valsartan + bisoprolol 3,44%. Based on the result of evaluation, found that the use of antihypertensive drug use considered as 100% right drug, 100% right patient, and 93,10% right dosage.